I Know You: User Profiling on Social Media Usage of Chinese Private University Students - Wang, Yunyan; Teo, Poh-Chuin (SCAD Independent, 2024)
Chinese university students’ use of social media is becoming increasingly diverse, and students from private universities in China have different group characteristics than those from public universities. This research endeavoured to establish a comprehensive user profile of Chinese private university students by examining their social media usage patterns. The purpose was to gain profound insights into the distinctive attributes of students in China’s private universities within the context of the current era characterised by extensive data availability. This study employed a questionnaire-based research approach to acquire a dataset consisting of 673 instances of social media usage among students enrolled in private universities in China. Subsequently, exploratory factor analysis was performed using the Statistical Package for Social Sciences (SPSS) software, extracting five (5) categorical feature tags. Combined with the extracted feature tags and the usage status and perception dimension data, the K-means cluster analysis method was used to perform rapid clustering to derive four (4) differentiated groups comprising information exchange-oriented users, instrument-oriented users, dependent-oriented users and entertainment-oriented users. Furthermore, thorough analysis and description of the essential attributes for these 4 user profile categories have been conducted by incorporating the fundamental user information.